Semi-state violent actors of Russia's invasion of Ukraine: the case of PMC Wagner: Semi-state violent actors of Russia's invasion of Ukraine: the case of PMC Wagner: A. Oleinik. - Oleinik, Anton (Crime, Law & Social Change, 2024)
The Wagner Group is a Private Military Company (PMC) funded by the Russian government and is actively involved in the war efforts against Ukraine. This case study highlights the contradiction between the requirements of secrecy and publicity in the operation of PMCs. Secrecy is needed to allow PMCs' home states to deny their involvement in conflicts abroad, plausibly or implausibly. To increase their client base, violent actors need a reputation. Building a reputation requires publicity. Characteristics of the Wagner Group lead to its being considered an extreme case of a semi-state violent actor. The Wagner Group case was studied using a mixed-methods approach combining quantitative and qualitative content analysis. A 60-million-word corpus of Russian political and media discourses about this country's invasion of Ukraine informed the study. The dataset covered the period from February 2022 to January 2024. Wagner's case study indicated the instability of the group's reputation and the dangers associated with the state's reliance on PMCs.